Quasi-empirical Methods of Efficiency, Prediction and Judgement in Plantation Forestry at Nepanagar - Khan, M. A. Waheed (Indian Forester, 1970)
Climate of the tropical dry zone creates environments which are not quite congenial for continued and accelerated growth DC plantation crops, particularly where such crops are dependent on annual precipitation. For the economic and industrial plantations, it is necessary that crops grow fast and produce the maximum utilizable wood volume per unit area and within the shortest possible period. The annual variability in rainfall conditions of the tropical dry zone is examplified with the climatic data of Nepanagar (M.P.). In order that the industrial plantations may prove an economic success, the first requirement is of a choice of a species. In this regard, merits of "Mysore Gum" are reviewed. Botanically, this species is said to be Eucalyptus tertticornis, yet in Nepanagar area the performance of pure E. tereticornis is not so plausible as that of "Mysore Gum".Appraisal of site factors is imperative to discover soil moisture build-up. A scheme to this effect is evolved, taking into consideration the soil type, topography and methods of soil working and planting. Inter-actions amongst these variables have been worked out as modifying factors for the actual annual precipitation. A simple procedure for the analysis of rainfall data is worked out to calculate the effective rainfall build-up from day to day. For most of the forest areas, calculations of this nature are possible, as rainfall records are usually available. For specific plantation centres, rain-gauges may also be installed for recording daily precipitation for a period of four months only, i.e., from lst June to 30th September each year.Instructions for running records of rainfall analysis are incorporated and the procedure for correlating soil moisture build-up with such forestry operations as date of planting, weeding, hoeing, mulching, application of chemicals as weedicides, termite repellents and killers, insecticides, fertilisers, etc., is given. Criteria are also laid down for judging the performance of plantations in anyone year. The use of rainfall analyses and soil moisture build-up in predicting suitability of different localities for plantation forestry is indicated.